1969
DOI: 10.1039/j29690000810
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of some αβ-unsaturated carbonyl compounds. Part I. Infrared spectra of acraldehyde, crotonaldehyde, methyl vinyl ketone, and ethylideneacetone

Abstract: Infrared spectra of acraldehyde, crotonaldehyde, methyl vinyl ketone, and ethylideneacetone in solution and vapour states are reported. Band intensity measurements at temperatures between -1 10" and 200" are interpreted in terms of conformational equilibrium between the s-trans and non-trans forms of the ketones. The additional enthalpy ( A H ) of the non-trans forms are : Methyl vinyl ketone EthylideneacetoneSolution in CS, Vapour 461 f 23 cal. mole-' 565 f 52 cal. mole-l 51 3 f 52 cal. mole-1 585 f 46 cal. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…Regio~z 3100-2700 em-' Most assignments in this region are similar to those already given for (E,E)-2,4-hexadiene (4). However, a 2808-cm-' band, which does not occur in (E,E)-2,4-hexadiene spectra, is assigned to the aldehydic CH stretching mode (v CHa) (12)(13)(14)(15)(16)(17). Another rather strong band at 2734 cm-' corresponds to the overtone of the deformation mode of the same CH group (2 6 CHa), in Fermi resonance with the v CHa (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resuits a N D Discussionmentioning
confidence: 97%
“…Regio~z 3100-2700 em-' Most assignments in this region are similar to those already given for (E,E)-2,4-hexadiene (4). However, a 2808-cm-' band, which does not occur in (E,E)-2,4-hexadiene spectra, is assigned to the aldehydic CH stretching mode (v CHa) (12)(13)(14)(15)(16)(17). Another rather strong band at 2734 cm-' corresponds to the overtone of the deformation mode of the same CH group (2 6 CHa), in Fermi resonance with the v CHa (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resuits a N D Discussionmentioning
confidence: 97%
“…5(g) [50]. As introducing CRAL vapor into IR cell containing pure SBA-15 wafer pre-treated with H 2 at 623 K, two characteristic bands at 1725 and 1711 cm À1 attributed to m(C@O) of unabsorbed or physicallyabsorbed CRAL molecule emerge and gradually diminish under continuous evacuation (Fig.…”
Section: Ft-ir Spectroscopic Studies Of Cral Adsorption and Hydrogenamentioning
confidence: 98%
“…The ratio of populations (s-cis/s-trans) increased with the bulkiness of the alkyl group (E:).2 Kossanyi3 reported that v C=O bands in all the AVK's and Y C=C bands in a'few AVK's were measured in pairs. Bowles et al 4 reported that v C-C, 6 CH=CH out of plane and 6 CH2 out of plane in the MVK were assigned with the two conformations. Katritzky et al5 reported the relation between the population of the conformations and the absorption coefficients of the v C=C bands ( A C=C) by assuming the A C=C value of the propenal and t-BuVK.…”
Section: Introductionmentioning
confidence: 97%